Chapter Economic inequality in Germany, 1500-1800 - Pfister, Ulrich (Datini Studies in Economic History, 2020)
The chapter reviews existing evidence regarding four aspects of economic inequality: relative factor rents, which relate to the factorial distribution of income and also underlie the so-called Williamson index (y/wus), which is correlated with the Gini index of household income; real inequality in terms of opposite movements of the price of consumer baskets consumed by different strata of society; the inequality of pay according to gender and skill, as well as between town and countryside; and wealth inequality, particularly with respect to the access to land. The main result is that, with given technology and agrarian institutions, there is a positive correlation between population and inequality.